Participatory Risk Assessment of Humpback Whale (Megaptera novaeangliae) and Leatherback Turtle (Dermochelys coriacea) Bycatch in Northern Peru - Costanza, Anna B.; Guidino, Chiara; Mangel, Jeffrey C.; Alfaro-Shigueto, Joanna; Verutes, Gregory; Caillat, Marjolaine; Samanta, Aritree; Hines, Ellen (Frontiers in Marine Science, 2021)
Uncertainties about the magnitude of bycatch in poorly assessed fisheries impede effective conservation management. In northern Peru, small-scale fisheries bycatch negatively impacts marine megafauna populations and the livelihoods of fishers. Within this area, humpback whale (HBW) (Megaptera novaeangliae) and leatherback turtle (LBT) (Dermochelys coriacea) populations experience bycatch mortality with little official reporting. By leveraging the experience and knowledge of local fishers, we used a low-cost participation mapping approach to provide a spatio-temporal assessment of bycatch risk for HBW and LBT off two Peruvian fishing ports. Using an open-source, geographic information systems based model, Bycatch Risk Assessment (ByRA), as our platform, the model outputs provided risk maps and gear risk percentages categorized as high, medium, and low for the study area within seven subzones for both species. Our map outputs indicate that bycatch management should be port specific, following seasonal and spatial variations for HBW, and specific fishing gear impacts for HBW and LBT. Given the traditional marginalization of small-scale fisheries BYRA could also serve as a method where fishers have a voice in local management measures.